PERFORMA TINDAK TUTUR ILOKUSI DALAM ANTOLOGI CERPEN REMAJA SUMATERA BARAT TAHUN 2015 - Sarmis, Miftahul Jannati; Tressyalina, Tressyalina; Noveria, Ena (Universitas Negeri Padang, 2018)
The purposes of study were toÂ (1) describe the forms of speech acts of illocution, (2) to describe the function of speech acts of illocution, and (3) to describe the narrative strategy used in the Summary Antim of Youth Teens of 2015. This type of research is qualitative by using descriptive method. The result of the research shows (1) The form of the act of speech illocution found that is representative, expressive directive, competetive declaration, convivial kolabotatif and conflict (3) strategy found that consist of speech act strategy speak frankly without without preamble tend to be used in context of utterance which is spoken by persons of equal standing and age. A straightforward, no-nonsense strategy of positive politeness tends to be used in the context of the speech that a younger character tells a younger character. The strategy of telling frankly without preamble to speak negatively tended to be told by an older figure to a younger character, already familiar in public. Vague-speaking strategies tend to be spoken by an older character to a younger character.Â Kata kunci: Performa, tindak tutur ilokusi, antologi cerpen,